Proposal of Breast Cancer / Haneesah Rostam and Fhathin Syazwanie Izhar - Rostam, Haneesah; Izhar, Fhathin Syazwanie (2008)
Breast cancer is a rapid, uncontrolled growth of abnormal cells in one or both breasts. It is the most common type of cancer in women, but it is often cured when found early. It is the second leading cause of cancer deaths in women today (after lung cancer) and is the most common cancer among women, excluding nonmelanoma skin cancers. According to the World Health Organization, more than 1.2 million people will be diagnosed with breast cancer each year worldwide and over 500,000 will die from the disease. The American Cancer Society estimates that 180,510 new cases of invasive breast cancer will be diagnosed in 2007. Breast cancer death rates have been dropping steadily since 1990, according to the Society, because of earlier detection and better treatments. About 40,910 breast cancer deaths are expected in 2007. According to the American Cancer Society, the chance that breast cancer will be responsible for a woman's death is about 1 in 33 (3%). The incidence rate of breast cancer (number of new breast cancers per 100,000 women) increased by approximately 4% during the 1980s but leveled off to 100.6 cases per 100,000 women in the 1990s. The death rates from breast cancer also declined significantly between 1992 and 1996, with the largest decreases among younger women. Medical experts attribute the decline in breast cancer deaths to earlier detection and more effective treatments